Have you ever listened coastal inhabitants? Know what they think… - Martins, F (2013)
Coastal dynamics changes, caused by natural or man-made factors, can to give rise serious consequences, namely at urban areas, exposing coastal population at risk. In this context, the understanding of the way people perceive the coastal dynamics and their exposure to risk is essential for the land use management and Integrated Coastal Zone Management. To get the perception of coastal population, this research was based in a risk map proposed by Water Institute (1999) that classifies the Portuguese territory in three categories of risk: low, mean and high. A questionnaire was applied to the dwellings owners in coastal risk areas of Praia de Esmoriz, Praia de Cortegaça, Furadouro, Torreira, Praia da Barra, Costa Nova do Prado and Praia da Vagueira, during the summer season, in 2006. The questionnaire has as main objectives: coastal risks social perception; coastal dynamics social perception; identification of territorial and environmental changes in the coastal areas; identification of socio-environmental conflicts. A total of 418 questionnaires were completed which corresponds to 10% of the dwellings at risk in the study area. Almost all of respondents recognize the shoreline retreat and would accept having their houses relocated if it were confirmed that there home was in fact in danger, however the inquired population confirms to feeling safe near the sea. In other words, there is negligence of the coastal risks. It is necessary to inform the population of the problems that the coastal areas are suffering of and to get everyone involved in coastal issues.